Assessing Fluency and Coherence in the Speaking Skill Of Street Verdor in Tourism Area - Marzuki, M. Junaidi; Maysuroh, Siti; Ghina Athiyyaturrahmah (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2024)
Using the IELTS rubric as a method for evaluation, the study aims to determine assessing the present fluency and coherence levels among the chosen street vendors based on the criteria specified in the IELTS rubric. Through a qualitative research design, the data collected from a sample population consisting of 9 street vendors from Kuta Mandalika. In order to collect the data, the researcher through interview test which consist of two part, dialogue and monologue each part lasted up to 3-5 minutes. The result showed that there were 3 part category to determine which are intermediate, limited and not competent. The intermediate result show 2 people in range 5.5-6.5 Band. Limited shows 2 people in range 4-5 Band and the rest of them are not competent. In conclusions all the participants were within the context of the "limited" assessment criteria. In computing the mean (average) of the numbers 2, 5, 6, 5, 3, 6, 4, 4, 3, the initial step involves summing these values to obtain a total of 38. Following this, the sum is divided by the total number of values, which is 9. This calculation yields a mean of approximately 4.22. Therefore, the mean of the dataset is approximately 4.22.